Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Ẩn danh

  Giúp e vs ạ

Nguyễn Lê Phước Thịnh
18 tháng 7 2024 lúc 10:46

\(\left\{{}\begin{matrix}x\left(1-\sqrt{3}\right)+y=2\\3x-\left(\sqrt{3}-1\right)y=1\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}x\left(1-\sqrt{3}\right)\left(\sqrt{3}-1\right)+y\left(\sqrt{3}-1\right)=2\left(\sqrt{3}-1\right)\\3x-\left(\sqrt{3}-1\right)y=1\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}x\left(-4+2\sqrt{3}\right)+y\left(\sqrt{3}-1\right)+3x-y\left(\sqrt{3}-1\right)=2\sqrt{3}-2+1\\3x-\left(\sqrt{3}-1\right)y=1\end{matrix}\right.\)

=>\(\left\{{}\begin{matrix}x\left(2\sqrt{3}-1\right)=2\sqrt{3}-1\\y\left(\sqrt{3}-1\right)=3x-1\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=1\\y=\dfrac{3x-1}{\sqrt{3}-1}=\dfrac{2}{\sqrt{3}-1}=\sqrt{3}+1\end{matrix}\right.\)


Các câu hỏi tương tự
Phương Thảo
Xem chi tiết
Phát Lê Tấn
Xem chi tiết
linh ngô
Xem chi tiết
Roseeee
Xem chi tiết
Roseeee
Xem chi tiết
Dorae mon
Xem chi tiết
Dorae mon
Xem chi tiết
Nguyễn Duy Thái
Xem chi tiết
Cho Hỏi
Xem chi tiết
dsađá
Xem chi tiết